2018
DOI: 10.1128/mbio.01006-18
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Variation of Rare Outer Membrane Protein β-Barrel Domains in Clinical Strains Provides Insights into the Evolution of Treponema pallidum subsp. pallidum , the Syphilis Spirochete

Abstract: In recent years, considerable progress has been made in topologically and functionally characterizing integral outer membrane proteins (OMPs) of Treponema pallidum subspecies pallidum, the syphilis spirochete, and identifying its surface-exposed β-barrel domains. Extracellular loops in OMPs of Gram-negative bacteria are known to be highly variable. We examined the sequence diversity of β-barrel-encoding regions of tprC, tprD, and bamA in 31 specimens from Cali, Colombia; San Francisco, California; and the Czec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 93 publications
6
57
0
1
Order By: Relevance
“…The prediction of treponemal protein structures is quite limited due to the lack of the protein homologues. However, a protein structure for tpr C was predicted by Centurion-Lara et al (2013) and more recently by Kumar et al (2018). The recombinant regions identified in the new tpr C3 and tpr C4 alleles found in this study (Supplementary Figure S2) correspond to the identified extracellular loops (L3, L4, L5) of the β-barrel outer membrane protein which were predicted to serve as B-cells epitopes 2 (Kumar et al, 2018; Figure 6).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The prediction of treponemal protein structures is quite limited due to the lack of the protein homologues. However, a protein structure for tpr C was predicted by Centurion-Lara et al (2013) and more recently by Kumar et al (2018). The recombinant regions identified in the new tpr C3 and tpr C4 alleles found in this study (Supplementary Figure S2) correspond to the identified extracellular loops (L3, L4, L5) of the β-barrel outer membrane protein which were predicted to serve as B-cells epitopes 2 (Kumar et al, 2018; Figure 6).…”
Section: Resultsmentioning
confidence: 72%
“…However, a protein structure for tpr C was predicted by Centurion-Lara et al (2013) and more recently by Kumar et al (2018). The recombinant regions identified in the new tpr C3 and tpr C4 alleles found in this study (Supplementary Figure S2) correspond to the identified extracellular loops (L3, L4, L5) of the β-barrel outer membrane protein which were predicted to serve as B-cells epitopes 2 (Kumar et al, 2018; Figure 6). Moreover, the newly predicted 3D structures of proteins TP0858 and TP0865 (Figure 6) revealed that the observed recombination-driven diversity almost strictly corresponds to the residues located at the host-pathogen interface.…”
Section: Resultsmentioning
confidence: 72%
“…In marked contrast to the OMs of Gram-negative bacteria, the T. pallidum OM is fragile, poorly antigenic, lacks lipopolysaccharide, and has a remarkably low density of integral OMPs [4,16,18,19]. In recent years, great progress has been made in characterizing syphilis spirochete's repertoire of rare, β-barrel-forming OMPs [16,[93][94][95]. The preponderance of T. pallidum-specific antibodies generated during human infection are directed against lipoproteins, not integral OMPs [3,21,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…pallidum OM is fragile, poorly antigenic, lacks lipopolysaccharide, and has a remarkably low density of integral OMPs [ 4 , 16 , 18 , 19 ]. In recent years, great progress has been made in characterizing syphilis spirochete’s repertoire of rare, β-barrel-forming OMPs [ 16 , 93 95 ]. The preponderance of T .…”
Section: Discussionmentioning
confidence: 99%
“…The coding change seen between the two isolates here (T260A) mapped to the POTRA3 domain. While the impact of amino acid substitutions in the TP0326 β-barrel on immunoreactivity has been studied [44,45], further work is required to understand the impact of the amino acid substitution observed in our isolates.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%